Better Anatomical and Cosmetic Results Using Tunneled Lotus Petal Flap for Plastic Reconstruction After Demolitive Surgery for Vulvar Malignancy. Issue 5 (1st June 2012) - Buda, Alessandro; Confalonieri, Pier Luigi; Rovati, Luca Carlo Vittorio; Fruscio, Robert; Giuliani, Daniela; Signorelli, Mauro; Dell'Anna, Tiziana; Pirovano, Cecilia; Milani, Professor, Rodolfo
Abstract : Objective: To evaluate the efficacy of tunneled lotus petal flap in terms of anatomical and cosmetic results in patients who underwent vulvoperineal reconstruction for vulvar malignancy. Methods: Between March 2010 and July 2011, 22 women underwent vulvoperineal reconstruction using tunneled lotus petal flap for primary or recurrent disease at San Gerardo Hospital, Monza. In 16 cases, lotus flaps were bilateral, whereas in 6 cases, they were monolateral. Results: The median age was 72 years (range, 53–87 years). The mean operating time was 85 minutes. The mean length of follow-up was 10 months (range, 2–16 months). Postoperative complications occurred in 2 patients, including one case of partial flap necrosis and one case of donor site breakdown. Conclusions: Tunneled lotus petal flap is safe, easy and fast to perform, has a low rate of complications, and good functional and cosmetic results. This technique represents an optimal solution for plastic reconstruction in case of primary or recurrent vulvar disease, or in case of introital stenosis after primary inadequate closure.